2013
DOI: 10.1186/1742-4690-10-69
|View full text |Cite
|
Sign up to set email alerts
|

Feline immunodeficiency virus latency

Abstract: Despite highly effective anti-retroviral therapy, HIV is thought to persist in patients within long-lived cellular reservoirs in the form of a transcriptionally inactive (latent) integrated provirus. Lentiviral latency has therefore come to the forefront of the discussion on the possibility of a cure for HIV infection in humans. Animal models of lentiviral latency provide an essential tool to study mechanisms of latency and therapeutic manipulation. Of the three animal models that have been described, the feli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 113 publications
0
22
0
Order By: Relevance
“…Table 1 summarizes key studies that have identified FIV cell reservoirs and the modalities used to detect infection or susceptibility to infection. It is important to note that the leukocyte subsets that have proven most consistently infected in vivo and susceptible to infection in vitro are CD4+ T cells and monocyte/ macrophages, which are also target cell reservoirs for HIV [13,49,54,[60][61][62]. Evidence thus far is conflicting regarding productive infection of dendritic cells in vivo [29,30,54,63], although multiple studies support productive FIV infection of cultivated dendritic cells [43,63,64].…”
Section: Cell Reservoirs Of Fivmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 summarizes key studies that have identified FIV cell reservoirs and the modalities used to detect infection or susceptibility to infection. It is important to note that the leukocyte subsets that have proven most consistently infected in vivo and susceptible to infection in vitro are CD4+ T cells and monocyte/ macrophages, which are also target cell reservoirs for HIV [13,49,54,[60][61][62]. Evidence thus far is conflicting regarding productive infection of dendritic cells in vivo [29,30,54,63], although multiple studies support productive FIV infection of cultivated dendritic cells [43,63,64].…”
Section: Cell Reservoirs Of Fivmentioning
confidence: 99%
“…Latently infected cells are thus of key importance when considering viral reservoirs, particularly within a host on ART. McDonnel et al reviewed FIV latency and the strengths of the FIV-infected cat as a model of the HIV-infected human [61]. Different cohorts of naturally and experimentally infected cats have demonstrated either undetectable or consistently detectable plasma viraemia during the asymptomatic phase, which may be due to differences in viral strains, inoculating dose, age of the animal or other factors [7,84,98,104,[115][116][117][118].…”
Section: Fiv Latencymentioning
confidence: 99%
“…Multiple molecular mechanisms may underlie the establishment and maintenance of latently-infected cellular reservoirs (Margolis, 2010), including epigenetic modification of histone proteins in chromatin (Colin and Van Lint, 2009; Imai et al, 2010; Margolis, 2010, 2011). FIV has been established as an outbred, large animal model of lentiviral latency, reviewed in (McDonnel et al, 2013). Studies in our laboratory demonstrated that domestic cats experimentally infected with FIV exhibit a state of latency in peripheral blood CD4+ T-cells with concurrent undetectable plasma viremia approximately 8 months after inoculation (Murphy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Use of the FIV-infected cat model of lentiviral latency may help address questions that are either logistically or ethically not feasible in HIV-infected humans, including the investigation of histone-modifying agents and other novel therapeutic antilatency approaches (McDonnel et al, 2013). Importantly, these findings have the potential to benefit FIV-infected cats as well as HIV-infected humans.…”
Section: Introductionmentioning
confidence: 99%
“…Quantification of plasma vRNA copy number was based on a standard curve previously described. [39] For assay of cell-associated vDNA and vRNA, real-time PCR assays of feline GAPDH were included in parallel using the same nucleic acid samples to normalize nucleic acid concentration as previously described. [11]…”
Section: Methodsmentioning
confidence: 99%